2009
DOI: 10.1007/bf03326102
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 2, 4, 6-trinitotoluene in aqueous solution by ozonation and multi-stage ozonation biological treatment

Abstract: ABSTRACT:The objective of this study was to explore the extent of 2,4,6-trinitrotoluene synthetic solution and red water mineralization by comparing conventional direct ozonation and multi-stage ozonation-biological treatment process. The alkaline hydrolysis was used for remediation 2, 4, 6-trinitrotoluene and red water at pH = 10.9. Nevertheless, the hydroxyl radicals would be generated by ozone decomposition with ozone dose of 0.177 g/L. The samples were subjected to chemical oxygen demand and total organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…H 2 O 2 concentration was determined by the DMP (2, 9-dimethyl-1,10-phenanthroline) method (Kosaka et al, 1998). (Gunten, 2003;Rosenfeldt et al, 2006;Tizaoui et al, 2007;Wu et al, 2007;Bandyopadhyay and Chattopadhyay, 2007;El Diwani et al, 2009). Therefore, these abnormal results could be due to interference by H 2 O 2 since overestimation was not observed during treatment with ozone alone or O 3 /UV.…”
Section: Methodsmentioning
confidence: 99%
“…H 2 O 2 concentration was determined by the DMP (2, 9-dimethyl-1,10-phenanthroline) method (Kosaka et al, 1998). (Gunten, 2003;Rosenfeldt et al, 2006;Tizaoui et al, 2007;Wu et al, 2007;Bandyopadhyay and Chattopadhyay, 2007;El Diwani et al, 2009). Therefore, these abnormal results could be due to interference by H 2 O 2 since overestimation was not observed during treatment with ozone alone or O 3 /UV.…”
Section: Methodsmentioning
confidence: 99%
“…The byproducts of advanced oxidation process have prevented this technique from general application though it is quite effective in removing MTBE (Acero et al, 2001). Granular activated carbon (GAC) adsorption is a widely used technology for treating water contaminated with many taste-and odor-causing organics and synthetic organic chemicals, either independently or coupled with biological degradation (Suffet and Wable, 1995;El Diwani et al, 2009). Some researches have reported that GAC could successfully remove MTBE from contaminated water (Wilhelm et al, 2002;Shih et al, 2003;Sutherland et al, 2004) mainly due to its well developed porous internal structure and large surface area (Yang and Al-Duri, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TNT and its derivatives can persist and accumulate over the long-term in nature and are difficult to biodegrade [1][2][3]. Therefore, biological methods combined with other pre-treatment methods, that are based on common microbiological methods, enzymes methods, or plant methods, have been developed for the treatment of TNTcontaminated wastewater and soil water [1][2][3][4][5][6][7][8][9][10][20][21][22]. Previous studies on TNT biodegradation used microorganisms, such as immobilized white rot fungi (Phanerochaete chrysosporium), for the treatment of TNT wastewater; biological aerated filters (BAF), anaerobic filters (AF), and anaerobic-anoxic-oxic moving bed biological reactors (A2O-MBBR) are commonly applied to wastewater treatment containing TNT in the next stage [1][2][3][4][5] after the wastewater has been pre-treated by physical or chemical methods.…”
Section: Introductionmentioning
confidence: 99%